2000
DOI: 10.1111/j.1499-1654.2000.001554.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Temporal Lobe Glucose Metabolism With the Wada Memory Test

Abstract: Summary: Purpose:The goal of the present study was to examine the relationship of 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) and the Wada memory test in lateralizing memory dominance and epileptic focus.Methods: FDG-PET and the Wada test were performed in 18 patients with temporal lobe epilepsy (TLE). The asymmetry indices of FDG-PET (PET-AI) were calculated in mesial, polar, anterolateral, midlateral, and posterolateral regions of the temporal lobe, and those of Wada memory test (Wada-AI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…1) [21]. The ROI of the whole temporal lobe was the sum of mesial, polar, anterior-lateral, mid-lateral and posterior-lateral ROIs.…”
Section: Methodsmentioning
confidence: 99%
“…1) [21]. The ROI of the whole temporal lobe was the sum of mesial, polar, anterior-lateral, mid-lateral and posterior-lateral ROIs.…”
Section: Methodsmentioning
confidence: 99%
“…Both, false positives (patients who failed the Wada without suffering postoperative amnesia) (Novelly and Williamson 1989) and false negatives (patients who passed the Wada but presented post‐operative amnesia) (Jones‐Gotman 1993, Loring et al 1990) have been reported. This may be attributable to the fact that the IAT preferentially perfuses lateral temporal regions and less frequently mesial temporal areas which include the hippocampus (Jeffrey et al 1991, Hong et al 2000). Similarly, the IAT may yield false results in patients with varying degrees of bihemispheric language representation (Oxbury and Oxbury 1984, Loring et al 1990).…”
Section: Invasive Methods Of Language and Memory Explorationmentioning
confidence: 99%
“…Furthermore, studies comparing PET with other procedures have yielded divergent results. On the one hand, Hong et al (2000), comparing FDG‐PET and Wada asymmetry indices in the same patients, found significant correlations between hypoperfusion in mesial temporal lobe regions and Wada memory lateralization. Similary, Hunter et al (1999) found that compared to IAT, the predictive value of PET for language lateralization ranged from 88 to 91 percent, based on visual inspection of the images by experienced neuroradiologists.…”
Section: Non‐invasive or Minimally Invasive Imaging Techniquesmentioning
confidence: 99%
“…The practical consequence of this finding for TLE surgery is that 18 FDG PET may have some predictive value regarding postoperative language and memory deficits [149], which are expected to be less severe when the temporal lobe was hypometabolic before operation. In fact, recent studies could correlate FDG-PET findings with the result of the intra-carotid amobarbital test [150,151].…”
Section: Mechanisms Of Interictal Glucose Hypometabolismmentioning
confidence: 99%
“…No relation between lateral temporal hypometabolism and hippocampal atrophy or neuronal loss as measured with MRI volumetry and histological studies, respectively Sackellares [128], Theodore [71], Radtke [139], Henry [154], Semah [155], Debets [14], O'Brien [156], Ryvlin [15], Salanova [141], Dlugos [157], Foldvary [158], Choi [159], Lamusuo [160], Theodore [161] Mesial temporal hypometabolism correlates with reduced hippocampal volume in TLE Knowlton [162] Temporo-polar hypometabolism correlates with reduced hippocampal volume in TLE Semah [155] Thalamus & putamen metabolism correlate with dentate granule cell density Dlugos [157] Lateral temporal hypometabolism correlates with white matter change on MRI in TL as well as microscopic cortical dysplasia in the lateral temporal cortex Latack [163], Stefan [72], Theodore [71], Ryvlin [80], Choi [159], Diehl [164], Chassoux [165] Relation with neuropsychological testing Correlated in the left temporal lobe with decreased verbal IQ and memory scores in TLE Raush [166] Correlated in prefrontal region with decreased verbal and performance intelligence Jokeit [167] Correlated with ipsilateral memory impairment on intracarotid amobarbital test Salanova [168], Hong [150], Salanova [151] Predictive of less severe verbal memory decline after lobectomy in left TLE Griffith [149] Reversibility after surgery Bilateral metabolic increase after surgey in mesial TLE Hajek [169] Decrease in the contralateral mesial TL after surgey in mesial TLE Hajek [169] Reversible in temporal neocortex after surgery in mesial TLE Hajek [169] Reversible in lateral TL cortex a...…”
Section: Relation With Hippocampal Atrophymentioning
confidence: 99%